Spatial pattern of pindó palm (Syagrus romanzoffiana) recruitment in Argentinian Atlantic Forest: the Importance of tapir and effects of defaunation - Sica, Yanina Vanesa (2014)
Hunting pressure, fragmentation and deforestation have caused global declines in animal abundance, and the consequences for plant communities are poorly understood. Many large-seeded plants, for instance, depend on large and endangered vertebrates for seed dispersal. In some Semi-deciduous Atlantic Forests, endangered tapirs (Tapirus terrestris) are major dispersers of pindó palms (Syagrus romanzoffiana). Here, we compare recruitment patterns of pindó palms between protected and disturbed (defaunated) Atlantic Forest areas in Argentina and evaluate the potential consequences of the lack of the main disperser for pindó palm regeneration. We analyzed the number and spatial pattern of pindó adults, offspring, and tapir dung piles within ten plots established in an area spanning tapir latrines inside Iguazú National Park and in a fragmented forest area outside the park where tapir is locally extinct. In both areas, we evaluated recruitment levels beneath 24 adult palms in circular plots centered on adult stems. We found lower pindó palm recruitment outside the park where offspring tended to be aggregated around adult palms. In contrast, in Iguazú National Park offspring were spatially associated with tapir dung-piles, in which most offspring were registered. Recruitment under adults was higher outside the park suggesting a lower rate of seed removal in disturbed areas. Our results show that tapir dispersal promotes higher recruitment levels of pindó offspring and shapes their spatial pattern, breaking the spatial association with adult (presumably maternal) palms. These results are useful for predicting the impact of local tapir extinction on this palm.